FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN KLIEN DENGAN HEMOPTISIS DI RSD KALISAT KABUPATEN JEMBER - Firdha Novitasari (Jurnal Kesehatan dr. Soebandi, 2014)
Tuberculosis (Hemoptysis) is the most common disease found in society today. Repeated hemoptysis should be suspected as a serious illness, so this causes anxiety for the client. The purpose of this study was to study the factors associated with anxiety in clients with hemoptysis in the Kalisat Kalisat International space at Jember Regency. This research design This study uses a "Cross Sectional" research design. In this study variable measurements were carried out at one time, where each subject was only observed once, that is, data was taken once and carried out in July 2012 in the Internal Room of Kalisat Hospital. Sample sample of 21 respondents with hemoptysis. Analysis of research data using the Linear Regression statistical test with a significance level of error of 5% or a significance level of 95%. Based on the relationship test conducted using the Linear Regression test, the significance value p = 0,000 was obtained, meaning that there was a relationship between age and anxiety level in patients with hemoptysis. Based on the relationship test conducted using the Linear Regression test, the significance value p = 0.003 means that there is a relationship between education and anxiety levels in patients with hemoptysis. Based on the relationship test conducted using the Linear Regression test, the significance value of p = 0.004 means that there is a relationship between work and anxiety levels in patients with hemoptysis. Need to do more in-depth research on the factors that influence the level of client anxiety. So that it can be arranged a special measurement tool in the measurement of anxiety levels that are better able to reflect the picture of the actual level of anxiety